Relational data clustering : models, algorithms, and applications - Long, Bo; Yu, Philip S.; Zhang, Zhongfei (Chapman & Hall/CRC data mining and knowledge discovery series, 2010)
Presents a comprehensive overview of relational data clustering in data mining research. This book reflects the emergence of relational data clustering as an important field of data clustering, with applications in text mining, social network analysis, collaborative filtering, and bioinformatics